STRATEGI BERTAHAN HIDUP DI MUSIM PACEKLIK PADA PETANI JAGUNG PIPILAN KERING DI DESA TUNAS PERACAK KECAMATAN BUNGA MAYANG KABUPATEN OGAN KOMERING ULU TIMUR. (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
Strategies to Survive in the drought season Dried corn farmer in the village of Bunga Mayang Tunas Peracak District of Ulu Ogan Ogan East. This study aims to calculate the income of corn farmers before and during the lean season to determine a survival strategy in the face of corn farmers famine in the village of Bunga Mayang Tunas Peracak District of East OKU District. The research was conducted in October until November 2015 held in the Village District of Bunga Mayang Peracak Tunas. The method used is a survey method using questionnaires as a data collection tool. Random sampling method (simple random sampling). The results showed the corn farmer's income before the lean season for Rp.8.653.170,00 per growing season. While the lean season when farmers' income by Rp.3.951.107,00 per growing season. While active strategy in the select farmers instance as many as 21 farmers instance, and Farmers who choose a passive strategy by 7 farmers instance, farmers who choose network strategy as many as 15 farmers of example, but farmers instance, there are doing more than one strategy for survival salama season famine lasted.